Effect of Awareness, Level of Understanding, Income Level, Tax Environment and Quality of Tax Services on Taxpayer Compliance in Paying Land and Building Taxes During the Covid-19 Pandemic in Kapasari Village, Surabaya - Endah Zhery Devianti; Ariyani (Jurnal Ekonomi, 2023)
For the purpose of this study is 1) to know and analyze the influence of taxpayer awareness on taxpayer compliance in paying the land tax and building, 2) to know and analyze the influence of taxpayer’s level of understanding on taxpayer compliance in paying the land tax and building, 3) to know and analyze the influence of taxpayer’s compliance with the land tax and building, 4) to know and analyze the influence of taxpayer’s compliance with the land tax and building, 5) to know and analyze the influence of taxpayer’s quality of taxpayer compliance on the land tax and building, 6) to know and analyze the influence of awareness variables, level of understanding, income level, income level, tax environment, and quality of tax service on the compliance of taxpayer’s paying the land tax and building. The object of this study is Compliance of Taxpayers in paying Earth Taxes and Buildings in Kapasari Village, Surabaya. The research method used is quantitative method. The total population in the study was 3,062 taxpayers, the sample method used is simple random sampling that researchers took from a population of 97 respondents using the Slovin formula. The sample data analyzed is the primary data, which will be processed using the SPSS application. For the results of the study, the level of understanding, the level of tax environment and the quality of tax services are significant, while the level of income partially does not have significant effect. Simultaneously awareness, level of understanding, income level, tax environment, and quality of tax services are significant. For the limitation in this study, it focuses on taxpayer respondents who own land and buildings in Kapasari Village, Surabaya and the influence on taxpayer compliance both partially and simultaneously.